Investigation of Relationships in the Children's Team in the Process of Sports Gaming - Voloshina, Lyudmila N.; Kondakov, Victor L.; Kopeikina, Evgeniya N.; Tretyakov, Andrey A.; Galimskaya, Olga G. (Journal of History Culture and Art Research, 2017)
The article presents the results of studying the children's readiness (in the age of 5-7 years old) to interact with peers and adults in the elementary sports and gaming activities. The study was carried out within the framework of the pilot program of the Russian Academy of Education, based on the pre-school educational institutions in the city of Belgorod. To study the relationship in the children's team we used observation, sociometric technique, and diagnostic game situation. The analysis of results obtained showed the presence of problems of readiness to interact with peers and the formation of a communicative component of social experience in children in the age of 5-7 years old. Namely: insufficient level of children's independence, limited ideas about the possibility of using the sports and gaming activities in their own experience, low level of social and normative behavior. The results of the study confirmed the data previously presented in the publications on the growth in the number of preschool children not capable to interpersonal interaction.